PENGARUH DESIGN PRODUCT, PERSONAL BRANDING, DISTRIBUTION, DAN DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN ALBUM K-POP (studi kasus pembeli pada Weverse Shop) - Ardhiza, Anabella Rieska; Setianingsih, Wahyu Eko; Izzudin, Ahmad (Growth, 2023)
In order to ascertain the impact of product design, personal branding, distribution, and digital marketing on purchasing choices for kpop albums on the Weverse Shop app, study was carried out. An electronic survey that was given to both women and men who had purchased K-pop records through the Weverse Shop program served as the basis for this study's quantitative approach, which included a purposive sampling method of 112 respondents. Multiple linear regression analysis, partial analyzing (t testing), and testing the coefficient of determination are all employed in data analysis (R2). The analysis's results, which were obtained using SPSS version 25, also reveal that while the distribution and digital marketing variables have a significant impact on buying behavior, the product design and personal brand variables have a significant effect.